La ética moral dialógica como artefacto perverso de gestión organizacional (2015)
This document is an approach to ethical and moral dilemma visible in organizations when making decisions, as two mutually opposing optical practices in administration frequently occur. This double perspective, dialogic or classically been addressed from a simplistic approach, an excessive attempt to override the underlying logic.